The Neuroprotective Effect of Amitriptyline on Radiation-Induced Impairment of Hippocampal Neurogenesis. Issue 4 (19th December 2019) - Guo, Yu Rong; Liu, Zi Wei; Peng, Shuang; Duan, Meng Yun; Feng, Jing Wei; Wang, Wei Feng; Xu, Yan Hua; Tang, Xi; Zhang, Xiang Zhi; Ren, Bo Xu; Tang, Feng Ru
The radioprotective effect of amitriptyline, an inhibitor of acid sphingomyelinase (ASMase), on radiation-induced impairment of hippocampal neurogenesis, loss of interneuron, and animal weight changes was investigated in BALB/c mice by immunostaining of biomarkers for cell division (Ki67), immature neurons (doublecortin or DCX), and interneurons (parvalbumin or PV) in the dentate gyrus (DG) of hippocampus. The results indicated that preirradiation (with 10 mg/kg, 2 times per day, for 7 consecutive days) or postirradiation (with 10 mg/kg, 2 times per day, for 14 consecutive days) treatment (pretreatment or posttreatment) with intraperitoneal injection of amitriptyline prevented the loss of newly generated neurons, proliferating cells, and interneurons in the subgranular zone of the DG. At the molecular level, pretreatment or posttreatment inhibited the expression of sphingomyelin phosphodiesterase 1 ( SMPD1 ) gene which codes for ASMase. The pretreatment for 7 days also prevented radiation-induced weight loss from 2 to 3 weeks, but not within 1 week after irradiation. On the other hand, the posttreatment with amitriptyline for 14 days could improve animal weight gain from 4 to 6 weeks after irradiation. The present study suggests that amitriptyline may be a promising candidate radio-neuroprotective drug to improve radiation-induced impairment of hippocampal neurogenesis and relevant neurological and neuropsychological disorders.